2017
DOI: 10.1007/s13197-017-2495-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-temperature long-time and high-temperature short-time blanching and frying treatments on the French fry quality of six Irish potato cultivars

Abstract: Processing conditions are an important determinant of French fry quality. However, the effect of low-temperature long-time (LTLT) and high-temperature short-time (HTST) blanching and frying treatments has not been investigated in many cultivars. The current study investigates the effect of the sequential application of these treatments on French fries processed from six Irish potato cultivars (Fianna, Innovator, Mondial, Navigator, Panamera and Savanna). Blanching was effected at 75 °C for 10 min or 85 °C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…Blanching temperatures and times depend on the blanching method, the initial properties of the matrix, the desired characteristics of the final product and the subsequent preservation method. Optimum blanching conditions can vary between the different fruits and vegetable kind but even between the different cultivars of the same kind (Ngobese, Workneh, & Siwela, 2017). Since there is no general rule for the optimum blanching time -temperature combinations as they can influence nutrients content, texture, color, shelf-life and other characteristics differently for each matrix, the two aforementioned combinations were selected in this study (Beveridge & Weintraub, 1995;Olivera et al, 2008;Patras, Tiwari, & Brunton, 2011) because HTST is a traditional process, while LTLT processes have been associated with improvement of texture due to activation of enzymes like pectin methylesterase (PME), or polygalacturonase (PG) (AbuGhannam & Crowley, 2006;Anthon & Barrett, 2006;Ni, Lin, & Barrett, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Blanching temperatures and times depend on the blanching method, the initial properties of the matrix, the desired characteristics of the final product and the subsequent preservation method. Optimum blanching conditions can vary between the different fruits and vegetable kind but even between the different cultivars of the same kind (Ngobese, Workneh, & Siwela, 2017). Since there is no general rule for the optimum blanching time -temperature combinations as they can influence nutrients content, texture, color, shelf-life and other characteristics differently for each matrix, the two aforementioned combinations were selected in this study (Beveridge & Weintraub, 1995;Olivera et al, 2008;Patras, Tiwari, & Brunton, 2011) because HTST is a traditional process, while LTLT processes have been associated with improvement of texture due to activation of enzymes like pectin methylesterase (PME), or polygalacturonase (PG) (AbuGhannam & Crowley, 2006;Anthon & Barrett, 2006;Ni, Lin, & Barrett, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Samples with a very low solid content and high fat content were less crispy and stickier (Kita et al 2007). Texture properties are influenced by different factors such as potato variety (Ngobese et al 2017), composition, frying temperature and type of oil (Kita et al 2005(Kita et al , 2007. Table 3 shows the average of hardness measurements, expressed as the maximum force to break the potato chip.…”
Section: Texturementioning
confidence: 99%
“…For examples, Alvarez et al (2000) and Zuo et al (2015) reported that blanching at 97 °C produced unacceptable sensory properties, high oil levels and inferior textural characteristics, while Mestdagh et al (2008) reported that blanching at 55-70 °C for 15-60 min improved the textural quality of French fries and lowered the oil uptake upon frying. Most previous blanching studies were conducted on French fries (Bingol et al 2014;Mestdagh et al 2008;Ngobese et al 2017;Zuo et al 2015). In our study, we used potato chips as the matrix for investigation.…”
Section: Introductionmentioning
confidence: 99%